2017
DOI: 10.2741/e794
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Alzheimer rsquo s disease with macular degeneration

Abstract: There is growing evidence of epidemiological, genetic, molecular and clinical links between Alzheimer's disease (AD) and age-related macular degeneration (AMD). Major interest in the relationship between AD and AMD has derived from the evidence that beta-amyloid, the main component of senile plaques, the hallmark of AD, is also an important component of drusen, the hallmark of AMD. This finding has a great potential in the present era of anti-amyloid agents for the treatment of AD. The connection between AD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Aging is the primary risk factor for both AD and AMD [ 38 ]. Oxidative stress is considered to be an imbalance between free radicals and antioxidants, which is the fundamental mechanism contributing to the aging process [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is the primary risk factor for both AD and AMD [ 38 ]. Oxidative stress is considered to be an imbalance between free radicals and antioxidants, which is the fundamental mechanism contributing to the aging process [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a correlation between AD and eye diseases other than AMD that includes glaucoma and susceptibility to diabetic retinopathy (30). Evolving key signaling disease mechanisms, include CFH, APOE (3133), and the matrix metalloproteinase pathway (34). Our data show that subretinal OAβ injection in mice triggers RPE cell damage and PRC loss after 7 d. To test the soundness of the Aβ deleterious effects on the RPE, we used human RPE cells in primary cultures and showed that it sets in motion similar damage as in the in vivo rodent.…”
Section: Discussionmentioning
confidence: 99%
“…The eye is a window to the brain, and they both share a common embryological origin and vasculature [11][12][13][14][15][16][17]. Eye diseases such as cataracts, glaucoma, macular degeneration, and diabetic retinopathy have been associated with AD in epidemiological studies, indicating that eye disease and AD possibly share common risk factors and pathological mechanisms at the molecular level [18][19][20][21][22]. The interconnections between the eye and the brain suggest that elucidating the common features of neurodegenerative processes can lead to a better understanding of both neurological and eye diseases [23].…”
Section: Introductionmentioning
confidence: 99%